Two Sides of Gender : Sex, Power, and Adolescence - Shah, Manisha (World Bank, Washington, DC, 2022)
Adolescents in Sub-Saharan Africa have some of the highest rates of intimate partner violence across the globe. This paper evaluates the impact of a randomized controlled trial that offers females a goal setting activity to improve their sexual and reproductive health outcomes and offers their male partners a soccer intervention, which educates and inspires young men to make better sexual and reproductive health choices. Both interventions reduce female reports of intimate partner violence. Impacts are larger among females who were already sexually active at baseline. The paper develops a game theoretic model to understand the mechanisms at play. In line with the model, the soccer intervention improves male attitudes around violence and sexual and reproductive health and reduces sexual activity. In the goal setting arm, females take more control of their sexual and reproductive health by exiting violent relationships. Females in this arm have higher quality partners at endline.